Low-capacitance StatCom with modular inductive filter - Farivar, Glen (2020)
In this paper, a cascaded H-bridge low-capacitance StatCom (LC-StatCom) with a modular inductive filter is introduced. Replacing the fixed-value filter inductors with thyristor-switched reactors, a well-developed member of the static VAR compensators family, reduces the overall energy storage capacity and voltage rating of the LC-StatCom without violating standard limits on current quality. The proposed modular inductive filter takes advantage of LC-StatCom's ability to synthesize high-quality ac voltage to reduce the overall energy storage requirement of the filter inductance. The proposed modular filter inductor concept adds an additional degree of freedom to control the maximum voltage drop on the filter inductor by changing the inductance value. This additional capability decreases the overall voltage rating of the converter. The effects of adding the modular inductor unit on the I-V characteristic of the LC-StatCom are evaluated. The effectiveness of the proposed solution is demonstrated by experimental results on a seven-level 0.7-kVA LC-StatCom.